Clinical outcomes of patients with salivary gland carcinomas preoperatively misdiagnosed as benign lesions. Issue 12 (9th March 2013) - Ryu, In Sun; Roh, Jong‐Lyel; Cho, Kyung‐Ja; Lee, Sang‐wook; Choi, Seung‐Ho; Nam, Soon Yuhl; Kim, Sang Yoon
<x xml:space="preserve">Abstract</x> Background We compared clinical outcomes between patients with salivary gland carcinomas preoperatively misdiagnosed as benign lesion and properly diagnosed as malignant lesion. Methods The outcomes were compared between patients with benign lesion and malignant lesion (44 each) on preoperative fine‐needle aspiration cytology diagnosis who underwent conservative or radical surgery. Results Five‐year lesion‐free survival (DFS) rates were 86.8% for benign lesion and 76.3% for malignant lesion (p = .128). Surgical extent did not significantly affect locoregional recurrence and DFS (p = .360). Univariate analysis showed that sublingual gland tumor, positive resection margin, and extraparenchymal extension (EPE) were significantly associated with DFS (p < .05 each). On multivariate analysis, EPE remained an independent variable (p = .047, hazard ratio = 6.621, 95% confidence interval = 1.393–31.474). Conclusions The clinical outcomes of patients with salivary gland carcinomas misdiagnosed as benign are relatively favorable. Conservative surgery may be sufficient for patients with low‐grade and T1–2 salivary gland carcinomas. © 2013 Wiley Periodicals, Inc. Head Neck 35: 1764–1770, 2013